Hydrogen and Strontium Isoscapes for the African Palearctic Range to Reconstruct Insect Migration and Connectivity - Ghouri, Sana (Université d'Ottawa / University of Ottawa, 2024)
Insect migration stands as a phenomenon of paramount ecological importance, influencing ecosystems through a myriad of mechanisms, from facilitating pollination to aiding at disease transmission. Many insect species undertake multi-generational migrations in the Afro-tropical and Palearctic ranges, and increasing evidence highlights a number of migratory circuits across the entire Afro-Palearctic. Yet unravelling the migratory connectivity of the successive generations of these insects remains challenging given the impossibility to apply traditional biologger technology (e.g., radiotelemetry, light loggers), because of the small size, short life span and often large population sizes and ranges of insects. To address this challenge, this research pioneers the application of dual stable isotopic geolocation techniques based on hydrogen (δ2H) and strontium (⁸⁷Sr/⁸⁶Sr). Isotope geolocation consists of comparing the isotopic signatures of a mobile individual (e.g., migratory insect) to a map predicting isotope variations on the landscape (i.e., isoscape). Consequently, applying isotope geolocation to reconstruct insect migratory routes and connectivity requires the development of isoscapes across the migratory circuit. We first developed a novel δ2H isoscape in insect wing tissues across the Afro-Palearctic range. We analyzed wing tissue from resident butterflies across the Afro-Palearctic. A strong linear relationship between δ2H in local known-origin butterfly wings and local growing-season precipitation δ2H values was found across the Afro-Palearctic allowing the development of a robust isoscape. However, the relationship was weaker in the Afrotropics due to the region’s unique environmental characteristics, notably highly variable evaporation rates and relative humidity. Achieving increased geolocation precision in this region will necessitate the development of novel modeling approaches, incorporating more time-specific environmental and climate data as well as combining other independent geolocation tools. To enhance the isotope geolocation potential of migratory butterflies across the Afro-Palearctic range, we developed a bioavailable strontium isoscape. Strontium isotope variations on the landscape are usually independent from those of hydrogen providing a second level of geolocation evidence and enhancing geolocation potential. To build a ⁸⁷Sr/⁸⁶Sr isoscape, we first compiled bioavailable ⁸⁷Sr/⁸⁶Sr data across the range and analyzed a series of plant samples to fill existing spatial gaps. We then applied a novel spatial interpolation ensemble machine learning approach to predict bioavailable ⁸⁷Sr/⁸⁶Sr ratios across the range. Our analysis emphasizes the influence of factors such as geology, lithology, soil properties but also desert dust and volcanic aerosol deposition on bioavailable ⁸⁷Sr/⁸⁶Sr. The novel ensemble machine learning approach outperforms the traditional random forest regression approach and provides a better assessment of spatial uncertainty to produce the most accurate and unbiased bioavailable ⁸⁷Sr/⁸⁶Sr isoscape across the Afro-Palearctic range. As a first test to demonstrate the potential of this dual δ2H-⁸⁷Sr/⁸⁶Sr geolocation approach, we applied it to study the migratory routes and connectivity of Vanessa cardui individuals collected from each side of the Sahara Desert. Dual isotope-based metrics elucidated painted lady migration across the Sahara in unprecedented detail, notably moderate population connectivity across the Sahara with dominance of latitudinal migratory trajectories, a leapfrog migration during the southern leg across the Sahara, and incremental shorter distance migration during the northern leg of the migratory cycle. The study also highlighted the important role of the Arabian Peninsula as a significant stepping-stone for individuals traveling between Europe, Africa, and Asia. Such patterns and knowledge of this species' connectivity level will help conservation practitioners better assess risks and improve conservation strategies. In conclusion, this thesis presents two novel isoscapes, each with a range of applications. The δ2H isoscape is applicable to trace regional dispersal or migration of insects across the Palearctic, including both bidirectional migration and one-way dispersive behavior. The ⁸⁷Sr/⁸⁶Sr isoscape provides a basis to study mobility across the African continent and is applicable not only to trace the mobility of terrestrial insects but also the origin of other animals, humans, and manufactured materials across Africa. Together those isoscapes considerably advance the possibility of reconstructing the mobility of migratory insects to solve novel questions as evidenced by our case study on painted ladies.
Keywords: hydrogen; strontium; isotope; isoscape; insect; migration; connectivity; Africa